EVALUASI HAPUSAN DARAH TEPI DARAH K3EDTA SEGERA DI PERIKSA DAN DI TUNDA 24 JAM DALAM SUHU 2-8C - Novi Ersanto; Adinda Dika Infantria; Titik Sundari; Andita Ayu Mandasari; Siti Nur Husnul Yusmiati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2023)
Since specimen collection, preanalytical factors such as time and temperature could affect the peripheral blood smear morphology of erythrocytes, leukocytes, and thrombocytes. Delays are often caused by the limited number of medical personnel so work is not properly organized. This research is an observational qualitative descriptive study to determine the morphology of blood smears immediately checked and delay 24 hours at 2-8 ?. This study aims to determine the evaluation of K3EDTA venous peripheral blood smears immediately checked and delayed 24 hours at 2-8?. From 25 K3EDTA blood samples of Maarif Hasyim Latif Sidoarjo University students, it was found that there were no changes in the morphology of erythrocytes and platelets. Meanwhile, in leukocyte cells, changes occur in the neutrophil segment and stab granules, which is the granules fade, and the leukocyte nuclei can still be identified properly, so that do not affect the examination results. In conclusion, the Evaluation of the K3EDTA Peripheral Blood Smear was immediately checked and delay 24 Hours at the temperature of 2-8 ? has no change, which is still within normal limits. Keywords : Blood Smear, Delayed, K3EDTA, Immediately checked